Cystic lymphangioma of pancreas: A rare case report and review of the literature. Issue 28 (July 2018) - Chen, Diyu; Feng, Xiaode; Lv, Zhen; Xu, Xiaofeng; Ding, Chaofeng; Wu, Jian
Abstract: Rationale: Lymphangiomas are benign lymphatic malformations that mostly occur in the neck and axillary regions. Abdominal lymphangioma is a rare type of this tumor, and pancreatic lymphangioma accounts for less than 1% of all lymphangiomas. In this report, we firstly reveal the application of ultrasound-guided puncture drainage combined with cell morphological examination for the diagnosis of pancreatic lymphangioma. Patient concerns: A 35-year-old male patient was admitted to our hospital with recurrent abdominal pain and general weakness for 1 week. From abdominal ultrasound (US) showed that a large cystic lesion occupied the abdomen, about 30.0cm×25.0cm, leading to suspicion of lymphatic cyst. Computed tomography (CT) was performed for further diagnosis and staging. Diagnoses: According to pathological findings in combination with immunohistochemical features, pancreatic lymphangioma was made. Interventions: To relieve symptoms of discomfort in the patient, distal pancreatectomy and splenectomy was carried out 1 week after the CT scan. Outcomes: The patient recovered to normal status within 19 days after surgery. Lessons: The abdominal cystic lymphangiomas are difficult to be differential diagnosed from other cystic lesions. And the origin of the tumor is also hard to be detected before operation. We should combine image and pathological examination to clarify a diagnosis. Although lymphangiomas are benign tumours, they can encroach on adjacent organs and grow to an enormous size and that, resection of these invaded organs may be required for a complete excision.